Flexoelectro-optic effect with large rotation angle of optic axis - Buczkowska, Mariola (Wydawnictwo Politechniki Łódzkiej, 2020)
The flexoelectro-optic effect in layers of chiral nematics was investigated numerically. The simulations concerned short pitch materials with the helix axis parallel to the layer plane. Configurations which allow to avoid accumulation of ions at the electrodes and are suitable for square-wave driving voltage were considered. They were related to large rotation angles of the optical axis of the layer about the normal to the layer. Influence of chosen parameters on efficiency of the electro-optic effect was studied.

Symulowano numerycznie efekt fleksoelektro-optyczny w warstwach nematyków chiralnych. Obliczenia dotyczyły materiałów o krótkim skoku, z osią helisy równoległą do płaszczyzny warstwy. Symulowano odkształcenia związane z dużymi kątami obrotu osi optycznej warstwy wokół normalnej do warstwy, które pozwalają uniknąć gromadzenia się jonów na elektrodach i kontrolować efekt elektrooptyczny napięciem prostokątnym. Zbadano wpływ wybranych parametrów na skuteczność tego efektu.
Efekt fleksoelektro-optyczny o dużym kącie obrotu osi optycznej
Keywords: chiral nematic; helical axis; flexoelectro-optic effect; chiralny nematyk; oś spiralna; efekt fleksoelektro-optyczny